Regulation of reproductive and behavioral plasticity in social insects - Long Ding; Yicheng Liu; Ching-Han Lee; Claude Desplan (Current Opinion in Insect Science, 2026)

Amine-functionalized oyster shell waste for hexavalent chromium removal and phosphate recovery - Kamonchanok Huangmee; Liang-Ching Hsu; Guan-Ru Liu; Pei-Chieh Tseng; Heng Yi Teah; Yu-Min Tzou; Nhu Anh Thi Than; Han-Yu Hsueh; Yu-Ting Liu (Bioresource Technology, 2026)

Development of a pomelo pectin–based microencapsulation system for Akkermansia muciniphila - Chang-Han Wang; Wen-Yu Liu; She-Ching Wu (Food Chemistry, 2026)

New features of Peristediidae fishes in the South China Sea - Han Tian; Hsuan‐Ching Ho; Pan Liu; Mingting Li; Wei Xie; Yane Jiang; Xingle Guo; Jiajie Chen; Junpeng Yang; Kedong Yin (Journal of Fish Biology, 2026)
Deep‐diving surveys enable observations of new features of behavioural and functional dimensions of the fish that are typically missing from specimen‐based taxonomy. This study documents three rare armoured searobins (Peristediidae: Scalicus engyceros , Paraheminodus murrayi , Peristedion liorhynchus ) in Xianbei Seamount, Zhongsha Islands and Shenhu Canyon in the South China Sea. Not seen in the dead specimen, the fish in life exhibits bizarre shrimp‐like (in common sense) morphology: the lip barbels formed a laterally rake‐like structure, and the pectoral fins functioned as legs that literally ‘walked’ on the sediment. The fish S. engyceros showed both sideways and backward walking. The paired pectoral fins extrude outwards laterally like flat plates, supporting body balance during walking and swimming. When disturbed, individuals escaped rapidly using both pectoral appendages and tail fins, combining shrimp‐like jerky movements with typical fish swimming. The same species have been reported to occur in both the North and South Pacific oceans, suggesting that their oceanic distribution is by larval dispersal via oceanic currents such as equatorial and Indonesian throughflow currents. The co‐occurrence of three congeners in the same sea may hint local geographic speciation at work after settlement in a seamount habitat.

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

White spot syndrome virus facilitates and relies on shrimp de novo nucleotide synthesis to support viral pathogenesis - Cong-Yan Chen; Der-Yen Lee; Shih-Shun Lin; Chun-Hung Liu; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Empagliflozin attenuates sorafenib-promoted renal ferroptosis and inflammation by targeting cyclooxygenase-2/prostaglandin E2 axis - Ming-Kai Tsai; Wen-Chin Lee; Shih-Chung Huang; Chao-Cheng Huang; Yi-Chen Wang; Chien-Han Yuan; Chih-Chiang Wang; Ching-Han Liu; Nan-Chieh Huang; Yi-Chen Chang; Cheng-Chieh Fang; Bi-Wen Yeh; et al. (Toxicology and Applied Pharmacology, 2025)

Anti-inflammatory glycosides from Gomphandra mollis Merr.: Structural elucidation and mechanistic insights - Quoc-Dung Tran Huynh; Thuy-Tien Thi Phan; Man-Hsiu Chu; Thanh-Vu Nguyen; Truc-Ly Thi Duong; Su-Jung Hsu; Yun-Han Wang; Ngoc-Thac Pham; Bien-Thuy Nguyen Bui; Dang-Khoa Nguyen; Thanh-Hoa Vo; Ta-Wei Liu; et al. (Phytochemistry, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Dynamic changes in the metabolome and microbiome during Citrus depressa Hayata liquid fermentation - Ta-Wei Liu; Benni Iskandar; Man-Hsiu Chu; Yun-Han Wang; Ting-An Huang; Su-Jung Hsu; Yves S.Y. Hsieh; Ching-Kuo Lee (Food Chemistry, 2025)

Macular pigments produced from microalga Chlorella sp. and applied to alleviate the pathogenic process in diabetic mice - Meng-Wei Lin; Wei-Hong Chiu; Cheng-Han Lin; Dung-Huan Liu; Pei-Ching Wu; Chih-Sheng Lin (Algal Research, 2024)

Hybridize magnesium-iron layered double hydroxide with biopolymers to develop multiple pathways for phosphate sorption and release: A potential slow release phosphorus fertilizer - Wen-Hui Li; Liang-Ching Hsu; Yu-Min Tzou; Yi-Chun Chen; Heng Yi Teah; Yu-Yu Kung; Han-Yu Chen; Yu-Ting Liu (Chemical Engineering Journal, 2023)

A sustainable layered nanofiber/sheet aerogels enabling repeated life cycles for effective oil/water separation - Ting Dong; Huabiao Ye; Wenhui Wang; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Photothermal and Concus Finn capillary assisted superhydrophobic fibrous network enabling instant viscous oil transport for crude oil cleanup - Ting Dong; Yanhui Liu; Na Tian; Yuanming Zhang; Guangting Han; Fudi Peng; Ching-Wen Lou; Shan Chi; Yanming Liu; Cui Liu; Jia-Horng Lin (Journal of Hazardous Materials, 2023)

Analyzing landslide-induced debris flow and flow-bridge interaction by using a hybrid model of depth-averaged model and discrete element method - Wen-Jie Shiu; Ching-Fang Lee; Chia-Chi Chiu; Meng-Chia Weng; Che-Ming Yang; Wei-An Chao; Chun-Yuan Liu; Cheng-Han Lin; Wei-Kai Huang (Landslides, 2023)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Lactobacillus plantarum PS128 Ameliorated Visceral Hypersensitivity in Rats Through the Gut–Brain Axis - Yen-Wenn Liu; Yen-Po Wang; Hsu-Fang Yen; Pei-Yi Liu; Wen-Jian Tzeng; Chia-Fen Tsai; Han-Chieh Lin; Fa-Yauh Lee; One-Jang Jeng; Ching-Liang Lu; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2020)

A panel analysis of the Mahjong card game and social activity with sleep-related measurements among Chinese older adults - Yen-Han Lee; Yen-Chang Chang; Mack Shelley; Ching-Ti Liu (Sleep and Biological Rhythms, 2020)

Evaluating the associations of consumption of non-red meat protein sources and flavor preferences on sleeping patterns among older adults in China - Yen-Han Lee; Yen-Chang Chang; Ching-Ti Liu; Mack Shelley (Sleep and Biological Rhythms, 2019)

Dietary patterns with fresh fruits and vegetables consumption and quality of sleep among older adults in mainland China - Yen-Han Lee; Yen-Chang Chang; Yi-Ting Lee; Mack Shelley; Ching-Ti Liu (Sleep and Biological Rhythms, 2018)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Increasing trend of the incidence of esophageal squamous cell carcinoma, but not adenocarcinoma, in Taiwan - Ching-Liang Lu; Hui-Chu Lang; Jiing-Chyuan Luo; Chun-Chu Liu; Han-Chieh Lin; Full-Young Chang; Shou-Dong Lee (Cancer Causes & Control, 2010)

Serial cytokine levels in patients with severe sepsis - Huang-Pin Wu; Chian-Kuang Chen; Kong Chung; Jo-Chi Tseng; Chung-Ching Hua; Yu-Chih Liu; Duen-Yau Chuang; Chung-Han Yang (Inflammation Research, 2009)

Glutamic acid 219 is critical for the thermostability of a truncated α-amylase from alkaliphilic and thermophilic Bacillus sp. strain TS-23 - Long-Liu Lin; Jai-Shin Liu; Wen-Ching Wang; Szu-Han Chen; Chih-Chen Huang; Huei-Fen Lo (World Journal of Microbiology and Biotechnology, 2008)

Cell Membrane Diversity in Noncovalent Protein Transduction - Betty Revon Liu; Jyh-Ching Chou; Han-Jung Lee (The Journal of Membrane Biology, 2008)

A Bacterial Indole-3-acetyl-L-aspartic Acid Hydrolase Inhibits Mung Bean (Vigna radiata L.) Seed Germination Through Arginine-rich Intracellular Delivery - Kevin Liu; Han-Jung Lee; Sio San Leong; Chen-Lun Liu; Jyh-Ching Chou (Journal of Plant Growth Regulation, 2007)